2001
DOI: 10.1063/1.1398100
|View full text |Cite
|
Sign up to set email alerts
|

Potential energy curves and dipole transition moments for electronic states of ArHe and HeNe

Abstract: Relativistic core-potential calculations have been carried out on the ground and excited ⍀ states of ArHe and HeNe correlating with the atomic limits Ar*(3p 5 4s, 3 P, 1 P) and Ne*(2p 5 3s, 3 P, 1 P), respectively, and with ground-state He atoms. The potential energy curves of the excited states of ArHe are repulsive. The potential energy curves of the 0 Ϫ ͑I͒, 1͑I͒ and 0 ϩ ͑II͒2p→3s states of HeNe show a local Rydberg minimum at 2.8 bohr and a barrier at 4.0 bohr, while the other excited state potentials of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…This conclusion can be confirmed by comparison with lifetimes for the 0 þ , 1 states produced by the interaction Neð2p 5 3s 3 P 2 ÞÀ Heð1s 2 Þ. According to [14], the spin-orbit interaction results in ¼ 18 ms in this case.…”
Section: Molecular Physics 761supporting
confidence: 76%
See 1 more Smart Citation
“…This conclusion can be confirmed by comparison with lifetimes for the 0 þ , 1 states produced by the interaction Neð2p 5 3s 3 P 2 ÞÀ Heð1s 2 Þ. According to [14], the spin-orbit interaction results in ¼ 18 ms in this case.…”
Section: Molecular Physics 761supporting
confidence: 76%
“…This value is equal to 6:5 Â 10 À7 0 , where 0 ¼ 2:0 Â 10 À2 s is the radiative lifetime of a single Heð2 1 S 0 Þ atom [13]. For comparison, the radiative lifetime corresponding to the local minimum in the excited 1ðIÞ state which correlates with the metastable 3 P 2 state of Ne plus ground state He is 18 ms [14].…”
Section: Results and Conclusionmentioning
confidence: 98%
“…The spin−orbit interaction is essential in removing the forbidden character of the He 2s-1s transitions in the presence of neon. As in earlier work, a two-step configuration interaction procedure , is employed to accomplish this task. First, Λ-S calculations are carried out at the multiconfiguration single- and double-excitation configuration interaction (MRD-CI) level of treatment with a spin-independent Hamiltonian for a large series of electronic states.…”
Section: Details Of the Calculationsmentioning
confidence: 99%
“…Probably the main reason why ab initio calculations are quite desirable in this type of study is that they represent the most promising means of also obtaining electric dipole transition moments for the processes of interest, which in turn are required for quantitative prediction of the intensities of these collisioninduced optical transitions. Petsalakis et al 10 made a first attempt in this direction for the HeNe system, but they only succeeded in obtaining accurate potentials and dipole moments for the relatively low-lying excited states that correlate with the 2p-3s Ne asymptotes. In the present study more extensive calculations are reported for higher-energy HeNe states that dissociate to both of the aforementioned He 1s-2s atomic limits as well as the neighboring species that correlate with the 2p-3p, 2p-4s, 2p-3d, 2p-4p, 2p-5s, and 2p-4d asymptotes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Как отмечено в [2], трудности связаны с тем, что энергии электронного возбуждения оказываются близкими к порогу ионизации, что приводит к необходимости в расчетах ab initio одновременного учета большого числа ридберговских диффузных орбиталей. В настоящее время расчеты в подходе ab intio существуют только для ограниченного набора пар взаимодействующих атомов, а именно ArNe, ArHe, ArKr [3][4][5]. Для рассматриваемых в работе пар Kr * + He, Xe * + He расчеты потенциалов взаимодействия в возбужденных состояниях на сегодняшний день в таком подходе отсутствуют.…”
Section: Introductionunclassified